Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together Terhadap Hasil Belajar Materi Aritmetika Sosial Kelas VII - Baiq Putri Ayu Wirenika; Baidowi Baidowi; Nyoman Sridana; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2021)
This research aims to (1) describe the learning result to students in grade VII SMP Negeri 2 kediri academic year 2019/2020. (2) to understand the influence of Numbered Heads Together (NHT) cooperative learning to the result of students learning mathematics. This research is experimental. The subjects are grade VII-B as the experiment class using the numbered heads together (NHT) type cooperative learning model and grade VII-C as the control class using the direct learning model. The student mathematics learning outcomes data on social arithmetic material in thisstudy are collected by using posttest. Analysis data test used polled variant test. As the result of the research, the average score of the experiment class (74.58) control class (68.80)with mastery learning outcomes in the experimental class 66.66% and in the control class 61.90%, which t_count=2.278 > t_tabel=1.671 with α = 5%. From the result of research that has been conducted, it can be seen that there is a difference brtween the control class and the experiment class in the results of students learning mathematics. So, it can be concluded that numbered heads together (NHT) cooperative learning influence student learning mathematics in social arithmetic grade VII academic year 2019/2020.